On the Abolition of the Death Penalty for Drug Offences in China - Yanbing Wang (Studies in Law and Justice, 2023)
The Criminal Law Amendment (VIII) Act and the Criminal Law Amendment (IX) Act abolished the death penalty for many non-violent crimes, in line with the provisions of our Constitution on “respecting and safeguarding human rights” and in line with the international trend towards abolition of the death penalty. However, unlike many of the non-violent crimes that have been abolished, drug offences, which are also non-violent crimes, remain on the list of capital punishment. Over the past two decades, many academic and judicial leaders have worked towards the abolition of the death penalty for drug offences. However, due to the myth of the deterrent effect of the death penalty for drug offences and the heavy-handedness of the traditional drug management system, the goal of abolishing drug offences has never been achieved. The author argues that the death penalty for drug offences, as a non-violent crime, should not be treated as the most serious crime in criminal law and should be abolished. The aim of this article is to discuss the author’s ideas and rationale for the abolition of the death penalty for drug offences and to suggest some possible measures or ways to abolish the death penalty for drug offences.